Interactivity and learning through gamification, clinical rounds and virtual labs - Matos Silva , Carlos Danilo Cardoso; Cardoso Matos Silva, Marcus Vinicius (Seven Editora, 2023)
Learning is a complex process, which involves several external factors such as the physical environment, institutional culture, assessment requirements, among others, and internal factors such as personal motivation, guidance in the learning process, individual conception of knowledge. The concept of learning refers to the acquisition or construction of knowledge or the development of skills and attitudes as a result of educational experiences such as classes, readings and research. The options for using active teaching-learning methodologies are numerous in the health area, whose integration between theory and practice fostered through active methodologies launches a new horizon of training possibilities, which becomes more solid and effective what is known for meaningful learning. The relationship with reality, as in the practice carried out in the virtual laboratory, facilitates the fixation of contents and promotes the development of critical thinking. The formative potential of the active methodology configures an important teaching strategy for health professionals, based on the expectation of accentuated autonomy, it is expected that they will be able to solve problems through a global analysis of the context of each case, as it happens in clinical rounds. The challenge facing teachers is to look for didactic tools that can be used in the classroom to make the educational environment increasingly dynamic and attractive, such as proposals that involve pedagogical games (gamifications), which help to increase level of interest and concentration in activities, communication, motivation and interactivity of students. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-128